Changing trends in antibiotic susceptibility pattern among clinical isolates of Pseudomonas species in a tertiary care hospital in Nepal - Hamal, Deependra; Bhatt, Dharm Raj; Shrestha, Rajani; HS, Supram; Nayak, Niranjan; Gokhale, Shishir; Parajuli, Sulochana (Annals of Clinical Chemistry and Laboratory Medicine, 2021)
Background: Pseudomonas spp is notoriously known to be important agent of hospital as well as community acquired infections. These organisms are resistant to many antibiotics by intrinsic and acquired mechanisms making infections difficult to treat. Regular surveillance of infection and antibiotic resistance patterns is necessary for selection of appropriate antibiotics for treatment. Methods: Non repeating Pseudomonas spp isolated from all clinical samples during the year 2017-2019 were included in the study. Identification of Isolates were done by standard conventional tests and antibiotics sensitivity test was done by Kirby-Bauer disk diffusion method following the CLSI guidelines, 2017. Results: A total of 42,545 specimens comprising of sputum, blood, pus, urine, body fluids and endotracheal tubes were processed during the entire 3 year period. There was significant increase (p-value <0.05) in yearly isolation rate of Pseudomonas spp i.e. 141(7.95%), 197(12.14%) and 303(15.69%) isolates in the year 2017, 2018, and 2019 respectively. Resistance rates of the isolates to cefoparazone sulbactam, Piperacillin Tazobactam, and Tobramycin was significantly decreasing (p-value <0.05). Overall resistance to ceftazidime (66.13%) was alarming. Decrease in MDR isolates were statistically significant over 3 years e.g. 32(22.69%), 31(15.73%) and 37(12.21%) isolates in the year 2017, 2018 and 2019 respectively (p-value <0.05). Conclusion: The rate of infection of Pseudomonas spp is significantly increasing. There was gradual decrease in number of resistant isolates and MDR isolates over the peri-od starting from 2017 to 2019 which is a favorable trend. The possible factors playing role have to be further studied, identified and promoted.